Getting around Brown : desegregation, development, and the Columbus public schools - Jacobs, Gregory S., 1969- (Urban life and urban landscape series., 1998)
"Getting Around Brown is both the first history of school desegregation in Columbus, Ohio, and the first case study to explore the interplay of desegregation, business, and urban development in America. Drawing on a broad range of sources, including over sixty interviews, the book details the causes and consequences of Penick v. Columbus Board of Education (1977). Gregory S. Jacobs argues that school desegregation in Columbus failed to produce equal educational opportunity, not because it was inherently detrimental to learning, but because it was intrinsically incompatible with urban development. As a consequence, the long-term health of the city school district was sacrificed to preserve the growth of the city itself. The resulting middle-class abandonment of urban education in Columbus produced an increasingly poor, African-American city school system and a powerful form of defensive activism within the overwhelmingly white suburban systems."